Charge transport properties of single-component and binary aromatic self-assembled monolayers with methyl and trifluoromethyl tail groups - Asyuda, Andika; Wiesner, Adrian; Wan, Xianglong; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
We studied charge tunneling rates across the singlecomponent and binary self-assembling monolayers (SAMs) composed of 4-methyl-4′-mercaptobiphenyl (CH3-BPT) and 4triﬂuoromethyl-4′-mercaptobiphenyl (CF3-BPT) on Au(111). The composition of the binary SAMs could be ﬂexibly tuned, accompanied by gradual variation of the work function between ∼4.45 eV (CH3-BPT) and ∼5.5 eV (CF3-BPT). The tunneling rate across the single-component CH3-BPT SAM was found to be notably higher (by 1.5−2 orders of magnitude) than in the CF3BPT case, while that across the binary SAMs varied progressively with their composition, between the values for the single-component monolayers and could, consequently, be ﬁne-tuned. The observed behavior was tentatively explained by the higher projected density of states at the position of the terminal tail groups in the CH3-BPT case compared to CF3-BPT and by the appearance of an internal electrostatic ﬁeld in the SAMs, leading to a change and renormalization of the energy-level alignments within the junction upon contact of the SAMs to the top EGaIn electrode. The extent of the latter eﬀect depends primarily on the characteristics of the strongly conﬁned two-dimensional (2D) sheet of dipolar tail groups at the SAM/top electrode interface. The height of the respective injection barrier is, however, unaﬀected by these characteristics, as follows from the values of the transition voltage, which do not change notably with the SAM composition. Analysis of the presented as well as literature data suggests that the position of a dipolar group in SAM-forming molecules has a signiﬁcant impact on the performance of the respective SAM in the context of molecular electronics.
Gesehen am 10.02.2022